2011
DOI: 10.1371/journal.pone.0014805
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Somatic Cell Nuclear Transfer Is Dependent on Compatible Mitochondrial DNA and Reprogramming Factors

Abstract: Interspecies somatic cell nuclear transfer (iSCNT) involves the transfer of a nucleus or cell from one species into the cytoplasm of an enucleated oocyte from another. Once activated, reconstructed oocytes can be cultured in vitro to blastocyst, the final stage of preimplantation development. However, they often arrest during the early stages of preimplantation development; fail to reprogramme the somatic nucleus; and eliminate the accompanying donor cell's mitochondrial DNA (mtDNA) in favour of the recipient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Also, it could be that the supplied factors may not localize properly in the recipient cytoplasm. An experiment resembling this one has been recently tried in a murine-to-porcine iSCNT system, whereby mouse ES cell extracts were injected along with a mouse nucleus into mtDNA-depleted recipient porcine oocytes 17 . This significantly improved cybrid development to the blastocyst stage, yet because there was more than one difference between the control and treated iSCNT embryos, it is difficult to conclude whether the improvement came from the mtDNA exchange, and/or from anything else contained in the extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it could be that the supplied factors may not localize properly in the recipient cytoplasm. An experiment resembling this one has been recently tried in a murine-to-porcine iSCNT system, whereby mouse ES cell extracts were injected along with a mouse nucleus into mtDNA-depleted recipient porcine oocytes 17 . This significantly improved cybrid development to the blastocyst stage, yet because there was more than one difference between the control and treated iSCNT embryos, it is difficult to conclude whether the improvement came from the mtDNA exchange, and/or from anything else contained in the extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Inter-species somatic hybrid cells between mouse and human have always been obtained (37,38), but the maintenance of mitochondrial genomes has been shown to require essentially a complete set of cognate chromosomes. It has been reported that bovine oocyte cytoplasm can support the introduced differentiated nucleus of sheep, pig, monkey, and rat (39), and the recent study of rabbit-human (15) and pig-mouse (14,40) also resulted in early embryonic arrest. As a result, the relationship of nucleus and mitochondria is a huge challenge that can solve the iSCNT problem.…”
Section: Incompatibility Of Nucleus and Mitochondria 145mentioning
confidence: 99%
“…This scenario does not exclude the possibility that the oocyte has also additional factors that operate exclusively for reprogramming. The inefficiency of interspecies SCNT may be used as argument that reprogramming relies on factors that are used for sperm processing (Jiang et al 2011). The oocyte from one species often fails to reprogram the nucleus from another species also due to mitochondrial incompatibilities, which interfere with correct EGA (Jiang et al 2011).…”
Section: The Elusive Reprogramming Factorsmentioning
confidence: 99%
“…The inefficiency of interspecies SCNT may be used as argument that reprogramming relies on factors that are used for sperm processing (Jiang et al 2011). The oocyte from one species often fails to reprogram the nucleus from another species also due to mitochondrial incompatibilities, which interfere with correct EGA (Jiang et al 2011). In contrast to the view supported by interspecies SCNT, there are factors that seem to be only required for the development of cloned embryos, such as DJ-1 (Table 1), a factor that is not needed for development in fertilized embryos, suggesting specific molecules to be recruited (Miyamoto et al 2011).…”
Section: The Elusive Reprogramming Factorsmentioning
confidence: 99%